Techno-economic Assessment of Solar-driven Polygeneration System for Agri-food Industries - Naveed, Muhammad; Eduardo A. Pina; Luis.M. Serra; Ana Lázaro (Jornada de Jóvenes Investigadores del I3A, 2024)
This paper examines the technical, economic and environmental assessment of a solar-driven polygeneration system (SDPS) of a dairy industry located in Tauste, Zaragoza, Spain. The results showed that the proposed SDPS has a solar fraction of 64.3% with a lower cost and lower greenhouse gas (GHG) emissions than conventional system.